Different Outcomes of Anti-VEGF Treatment for Neovascular AMD according to Neovascular Sutypes and Baseline Features: 2-Year Real-Life Clinical Outcomes. (25th May 2021) - Arrigo, Alessandro; Saladino, Andrea; Aragona, Emanuela; Mercuri, Stefano; Introini, Ugo; Bandello, Francesco; Parodi, Maurizio Battaglia
Abstract : Purpose . To evaluate the effects of anti-VEGF treatment of neovascular age-related macular degeneration (nAMD) in a real-life clinical setting. Methods . Study design is a retrospective case series. Naïve nAMD patients treated with intravitreal injection of aflibercept or ranibizumab were analyzed over a 24-month follow-up. Each patient received the loading dose, followed by a PRN regimen. Patients were further subdivided into subgroups according to macular neovascularization type, best corrected visual acuity (BCVA) at baseline (BCVA > 0.3   LogMAR and BCVA ≤ 0.3   LogMAR ), and different anti-VEGF drugs. Primary outcome was the changes in BCVA and central macular thickness (CMT) over 24 months. Secondary outcomes included the influence of the selected drug and of the baseline BCVA on the final outcomes. Results . 439 patients (224 males; 51%) with naïve AMD-related macular neovascularization were included in the analyses. Mean age was 78 ± 8 years old. Compared to baseline evaluations, not significant BCVA changes were found at 1-year and 2-year examinations. CMT was significantly reduced at both 1-year and 2-year follow-ups (p < 0.01 ). Classic, polypoidal choroidal vasculopathy and mixed subtypes significantly correlated with worse visual outcome (p < 0.01 ). Overall, baseline BCVA significantly correlated with both 1-year and 2-year follow-up changes (p < 0.01 ). Moreover, BCVA at 1-year significantly correlated with BCVA changes at 2-year follow-up (p < 0.01 ). Furthermore, CMT changes from baseline significantly correlated with both 1-year and 2-year follow-up measurements (p < 0.01 ). Conclusion . Anti-VEGF approach is generally effective in stopping nAMD progression in our real-life analysis. No difference was found comparing patients treated with ranibizumab and aflibercept, nor in patients with drug switching.